HYAL1 deficiency attenuates lipopolysaccharide-triggered renal injury and endothelial glycocalyx breakdown in septic AKI in mice - Hongxia Xing; Shensen Li; Yongchao Fu; Xin Wan; Annan Zhou; Feifei Cao; Qing Sun; Nana Hu; Mengqing Ma; Wenwen Li; Changchun Cao (Renal Failure)
Background Renal dysfunction and disruption of renal endothelial glycocalyx are two important events during septic acute kidney injury (AKI). Here, the role and mechanism of hyaluronidase 1 (HYAL1) in regulating renal injury and renal endothelial glycocalyx breakdown in septic AKI were explored for the first time.Methods BALB/c mice were injected with lipopolysaccharide (LPS, 10 mg/kg) to induce AKI. HYAL1 was blocked in vivo using lentivirus-mediated short hairpin RNA targeting HYAL1 (LV-sh-HYAL1). Biochemical assays were performed to measure the levels and concentrations of biochemical parameters associated with AKI as well as levels of inflammatory cytokines. Renal pathological lesions were determined by hematoxylin-eosin (HE) staining. Cell apoptosis in the kidney was detected using terminal-deoxynucleoitidyl transferase-mediated nick end labeling (TUNEL) assay. Immunofluorescence and immunohistochemical (IHC) staining assays were used to examine the levels of hyaluronic acid in the kidney. The protein levels of adenosine monophosphate-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) signaling, endothelial glycocalyx, and autophagy-associated indicators were assessed by western blotting.Results The knockdown of HYAL1 in LPS-subjected mice by LV-sh-HYAL1 significantly reduced renal inflammation, oxidative stress, apoptosis and kidney dysfunction in AKI, as well as alleviated renal endothelial glycocalyx disruption by preventing the release of hyaluronic acid to the bloodstream. Additionally, autophagy-related protein analysis indicated that knockdown of HYAL1 significantly enhanced autophagy in LPS mice. Furthermore, the beneficial actions of HYAL1 blockade were closely associated with the AMPK/mTOR signaling.Conclusion HYAL1 deficiency attenuates LPS-triggered renal injury and endothelial glycocalyx breakdown in septic AKI in mice.